ETR 300 : Integrated Dynamic & Co Public Accounting / Arnida Alias ... [et al.] - Alias, Arnida; Ibrahim, Norfazilah; Zakaria, Siti Aisyah; Abu Bakar, Shaiful Azhar (2001)
Integrated Dynamic & Co is a business partnership which is consist of five member partners as our company leader. We are specializing in accounting services. Before the company being commenced we had already registered as on authorized audit firm with Malaysia Institute Of Accounting (MIA) on 1 November 2001.